Achondroplasia in sibs of normal parents. Issue 12 (December 1988) - Philip, N; Auger, M; Mattei, J F; Giraud, F
Abstract : A new case of recurrent achondroplasia in sibs of normal parents is reported. Two sisters and a half sister were affected. Various mechanisms can be postulated to account for unexpected recurrence of achondroplasia in the same sibship. Germinal mosaicism and unstable premutation are discussed here.